(untitled)
A field experiment was conducted in Ershadiyeh in a sedimentary soil with a mixture of clay and silty texture inthe winter season. 2005-2004 to determine the best concentration of nitrogen and potassium to spray onThe vegetation of the wheat plant, cultivar Ibaa 95 - in the two stages of inflorescence and flowering and complementaryof fertilization and their effect on dry matter accumulation and the percentage distribution of nitrogen concentration.in the shoot of wheat plants.A factorial experiment was carried out with a completely randomized block design, RCBD, which included fourThe concentration of nitrogen is 6000, 5000, 4000, 0